Beyond Financial Literacy: FoMO and Hedonic Lifestyle Drive Generation Z Impulsive Buying - Muhammad Iqbal Rifai; Siti Nur Qomariah (LPPM Universitas KH A. Wahab Hasbullah, 2026)
Impulsive buying among Generation Z students has become a pressing concern within the expanding fashion e commerce landscape in Indonesia. This study investigates the influence of financial literacy on impulsive buying behavior, with fear of missing out (FoMO) and hedonic lifestyle serving as mediating variables, among Generation Z students in Jombang Regency. A quantitative explanatory research design was employed using Partial Least Squares Structural Equation Modeling (PLS SEM), with data collected from 155 students across four Islamic background universities through proportionate purposive sampling. Instruments were distributed via Likert scale questionnaires through Google Forms. Findings reveal that financial literacy exerts no significant direct effect on FoMO, hedonic lifestyle, or impulsive buying. In contrast, both FoMO and hedonic lifestyle positively and significantly influence impulsive buying, with hedonic lifestyle demonstrating a stronger effect (path coefficient = 0.412, p < 0.001) compared to FoMO (path coefficient = 0.221, p = 0.004). Neither FoMO nor hedonic lifestyle mediates the relationship between financial literacy and impulsive buying, as the upstream paths from financial literacy to both mediators were statistically insignificant. These results suggest that impulsive buying in Generation Z is predominantly driven by emotional and lifestyle-oriented factors rather than cognitive financial considerations, underscoring the necessity of holistic behavioral interventions that extend beyond financial literacy programs.